Perceived buyer confidence in buyer-supplier relationships - Emmanuel Chao; Mshumbusi Paul Kato (jbm - Journal of Business Market Management, 2014)
Despite the importance of confidence in business relationship, very few scholars have empirically investigated the antecedents of this concept. In line with previous literature, this paper maintains that trust and control are the key sources for confidence. We use networks and reputation as indicators for trust, and ex ante contractual efforts and ex post contractual specifications as indicators for control. All these indicators have a positive impact on confidence. Trust and control seem to supplement each other as sources for confidence.
urn:nbn:de:0114-jbm-v7i4.969
Keywords: 650; Perceived buyer confidence; Networks; Ex-ante contractual term specificity; Ex- post contractual term specificity; Reputation